Keefektifan Model Flipped Classromm terhadap Pemahaman Konsep Fikih (Studi Analisis Model Pembelajaran pada Masa Pandemi Covid-19) - Suhartono Suhartono; Ady Alfan Mahmudinata (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
The purpose of this study was to test the effectiveness of the flipped classromm model on understanding the concept of fiqh among students during the Covid-19 pandemic. This study uses a quasi-experimental type of research. This research was conducted on fiqh learning. The research subjects were students of class VI at MI Darussalam Sambiroto, Baron, Nganjuk. Sampling using saturated sampling technique and hypothesis testing using the one-way Anova test with the help of the SPSS application. The results of the study show that the flipped classroom model is effective for understanding students' concepts of fiqh learning materials. The effectiveness of the flipped classroom model is shown from (1) the results of the learning implementation score of the flipped classroom model with an average score of 100 or good category; and (2) the average value of the fiqh concept understanding test of students in the class taught using the flipped classroom model is 80.52, which is better than the average value of the expository model is 70.35 and the significance value is 0.00 or less than 0, 05 (0.00 < 0.05), then there is a difference in the effectiveness of the two learning models, where the flipped classroom model is more effective in understanding students' fiqh concepts. The flipped classroom model can be applied in various lessons and in various situations and conditions, including during the covid-19 pandemic.